Memorandum of agreement between Universiti Teknologi MARA and the Government of Malaysia / Fakulti Perubatan - Universiti Teknologi MARA, Fakulti Perubatan (Universiti Teknologi MARA (UiTM), 2018)
Memorandum of agreement for the teaching and training of students pursuing medical studies at undergraduate level in UiTM at the government hospitals and health facilities.